2020
DOI: 10.21037/qims-19-835
|View full text |Cite
|
Sign up to set email alerts
|

Age-related fatty infiltration of lumbar paraspinal muscles: a normative reference database study in 516 Chinese females

Abstract: Background: Fatty infiltration, as a result of aging, is an essential biomarker of muscle degeneration. This research aimed to investigate the age-dependent change of fatty degeneration in the paraspinal muscles of healthy Chinese women. This study also explores the effect of body size on fatty infiltration of paraspinal muscles. Methods: Cross-sectional area of paraspinal muscles (CSA muscle ) and intermuscular adipose tissue (CSA IMAT ) were measured at the L3 mid-vertebral level of 516 healthy females, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…An age-related increase of IMAT of the quadriceps muscle of elderly inpatients (> 65 years) was also reported using ultrasound [ 28 ]. In abdominal CT images of Chinese women, Peng et al [ 29 ] showed an age-related increase of IMAT and a decrease of muscle cross-sectional area of the paraspinal muscles. An age-related increase of paraspinal FF has also been detected by MRI [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…An age-related increase of IMAT of the quadriceps muscle of elderly inpatients (> 65 years) was also reported using ultrasound [ 28 ]. In abdominal CT images of Chinese women, Peng et al [ 29 ] showed an age-related increase of IMAT and a decrease of muscle cross-sectional area of the paraspinal muscles. An age-related increase of paraspinal FF has also been detected by MRI [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although MRI is more commonly used, several previous studies have used CT for the evaluation of FI and reported the reliability of CT evaluation [6][7][8][9]. The CSA and FI of the lumbar muscles are associated with age, sex, body mass index (BMI), and LBP [10][11][12]. In a previous study, the FI could be measured as the ratio of FCSA to gross cross-sectional area (GCSA) [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the FI% of the paraspinal muscles gradually increased with aging. Peng et al used the qCT imaging to investigate 516 Chinese females, and they found that the fatty infiltration of the paraspinal muscles increased with aging [ 20 ]. The erector spinae are primarily more vertical in comparison to the multifidus, which means that they might bear more pressure.…”
Section: Discussionmentioning
confidence: 99%